The transition to sustainable living and practice - Leonard, Liam; Barry, John, 1966- (Advances in ecopolitics ;, 2009)
"The Transition to Sustainable Living and Practice" provides a series of insights into real alternatives to the current economic malaise, with an examination of key themes such as transition towns, traditional villages, new green financial concepts, the sustainable utopia, co-operative farming, sustainability and activism, ecofeminism, green protectionism, intentional communities and a green philosophy of money.